A Study Of The Effectiveness Of Total Quality Management Implementation In FICO Asia How TQM Tools Can Be Used Effectively In Economy Downturn Situation To Overcome Human Morale Issue - Chee, Liaw Ming (2002)
This dissertation is a study of the effectiveness implementation of Total Quality Management (TQM) in Fico Asia and how TQM tools can be used effectively in economy downturn situation to overcome human morale issue in Fico Asia. It is based on the existin